Realities, Challenges, Visions? Towards a New Foreign Cultural and Educational Policy - Robertson-von Trotha, Caroline Y. (WIKA Report, 2022)
Changing realities, global power shifts, and societal upheavals are resulting in new tasks and challenges for Foreign Cultural and Educational Policy. In an age of globalisation, digitisation, and growing nationalism, there is a particular need to inquire into the notion of responsibility and available spaces of action: How can strategies and networks for successful international and intercultural cooperation be drawn up, and what role do civil society actors play?